Nuclear Desire: Power and the Postcolonial Nuclear Order - Shampa Biswas (University of Minnesota Press, 2014)
â€œOrderâ€ and â€œdisorderâ€ have shaped the nuclear world. Nuclear fission is the process of splitting the center of an atom to set in motion a process of radioactive decay. The remarkable scientific discovery of how to make and sustain such a chain reaction to generate incredible amounts of energy produced some of humankindâ€™s loftiest aspirations as well as its most apocalyptic nightmares. In its utopian incarnation of nuclear energy, nuclear fission can solve our most pressing energy needsâ€”it can deliver us from the environmental limits of relentless capital accumulation and consumerism and, indeed, reign us back from the portending dystopia of global climate change. But in its dystopian incarnation, nuclear fissionâ€”now not so well contained within an exploding concrete structure (Fukushima Daiichi), now in the form of uncontrolled destruction inflicted on hapless innocents (Hiroshima and Nagasaki)â€”becomes a nuclear nightmare. An appreciation for this enormous potential of nuclear decentering and the desire to harness its possibilities and control its dangers generated a â€œglobal nuclear order,â€ centered on a much-celebrated and extremely important treatyâ€”the Nuclear Non-Proliferation Treaty (NPT). The NPT was one among many efforts to craft a global nuclear order to restrain the dangers of nuclear power, while liberating its â€œpeacefulâ€ possibilities for the larger collective good.